2022
DOI: 10.1016/j.apnu.2021.11.001
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of body image and depression among adults during COVID-19: A moderation model

Abstract: Background Since many aspects of functioning can affect body image, the aim of our study was to assess whether the relationship between body image-related negative emotions or depression and body dissatisfaction was moderated by body image-related quality of life and to compare these analyses among participants with various body mass index during COVID-19. Subjects and methods One hundred and thirty-one adults participated in the study. Measurement tools included the Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…The test-retest follow-up period used is shorter than what has been employed for some other psychometric evaluations, but a 3 to 6 days interval is considered sufficiently long, as no statistical differences are observed between such an interval and longer periods. 10 What is more, the questionnaires were designed originally for UK/U.S. populations with some political and cultural differences from the Polish population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The test-retest follow-up period used is shorter than what has been employed for some other psychometric evaluations, but a 3 to 6 days interval is considered sufficiently long, as no statistical differences are observed between such an interval and longer periods. 10 What is more, the questionnaires were designed originally for UK/U.S. populations with some political and cultural differences from the Polish population.…”
Section: Discussionmentioning
confidence: 99%
“…Although a few tools measuring body image are available in the Polish language, e.g., the Body Appreciation Scale-2 (BAS-2), 9 the Body Image Quality of Life Inventory (BIQLI; both used for the convergent validity in our work), 10 the Multidimensional Body-Self…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BI is a multidimensional construct that refers to an individual’s subjective representation of their body [ 14 , 15 , 16 ]. Evidence showed that a negative BI may be correlated with a high level of mental disorders such as anxiety and depression, as well as low self-esteem [ 17 , 18 ]. Moreover, self-reported studies demonstrated that participating in PA can positively affect perceived BI among adults [ 11 , 16 ].…”
Section: Introductionmentioning
confidence: 99%